2014
DOI: 10.1097/ccm.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Infection Hospitalization Increases Risk of Dementia in the Elderly*

Abstract: Objectives Severe infections, often requiring intensive care unit (ICU) admission, have been associated with persistent cognitive dysfunction. Less severe infections are more common and whether they are associated with an increased risk of dementia is unclear. We determined the association of pneumonia hospitalization with risk of dementia in well-functioning older adults. Design Secondary analysis of a randomized multicenter trial to determine the effect of Gingko biloba on incident dementia. Setting and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(107 citation statements)
references
References 51 publications
7
98
2
Order By: Relevance
“…Another challenge is the way infections of the lungs compromise the oxygen and carbon dioxide exchange, followed by symptoms of confusion and irritability [6]. These patients may have a degree of infection so severe that it limits their ability to participate in a study.…”
Section: Physiology Of Cognitionmentioning
confidence: 99%
See 4 more Smart Citations
“…Another challenge is the way infections of the lungs compromise the oxygen and carbon dioxide exchange, followed by symptoms of confusion and irritability [6]. These patients may have a degree of infection so severe that it limits their ability to participate in a study.…”
Section: Physiology Of Cognitionmentioning
confidence: 99%
“…In addition to factors such as degree of the illness, age, or other reference points, sound mentation measurement tools must be used, or the patient may fail to internalize the framed message. Recent secondary analysis by Tate and Snitz [6] explored N=3,069 patients hospitalized with pneumonia, and found that the pneumonia increased their risk for dementia. The findings showed that 17% of patients with pneumonia develop dementia.…”
Section: Challengesmentioning
confidence: 99%
See 3 more Smart Citations